Evaluation of the accuracy of shooting skills from a standing position for under-15 football players in Al- Khums city - Ibrahim Milad Jibril Mohammed (Journal of Libyan Academy Bani Walid, 2025)
Assessment of Shooting Accuracy from a Set Position for Under-15 Football Players in the City of Al Khums This study aimed to identify the skill level of shooting accuracy from a set position for under-15 football players in the city of Al Khums. The researchers employed the descriptive method using a purposive sample of 15 players from Al-Reef Football Club's under-15 team. The Shooting Accuracy Test from a Set Position (Squares Test) was used as the primary measurement tool. The results showed that the overall approximate mean score for the players was at a "Good" level (11.93 points). The performance level analysis indicated that 60% of the sample fell into the "Very High" and "High" categories, suggesting that the general performance level was above average. Furthermore, 20% of the sample achieved an outstanding performance (14−15 points). Despite this good level, nconsistency in skill performance was noted among some players due to fluctuating results across attempts. The researchers concluded that most players possess the acceptable minimum skill level and that the overall performance suggests coaches' attention to this skill. The study recommended holding training courses for coaches of youth categories and prioritizing the mastery of fundamental skills before engaging young players in competitions